Lifestyle physical activity among urban Palestinians and Israelis: a cross-sectional comparison in the Palestinian-Israeli Jerusalem risk factor study - Merom Dafna; Sinnreich Ronit; Aboudi Vartohi; Kark Jeremy D; Nassar Hisham (BMC, 2012)
Abstract Background Urban Palestinians have a high incidence of coronary heart disease, and alarming prevalences of obesity (particularly among women) and diabetes. An active lifestyle can help prevent these conditions. Little is known about the physical activity (PA) behavior of Palestinians. This study aimed to determine the prevalence of insufficient PA and its socio-demographic correlates among urban Palestinians in comparison with Israelis. Methods An age-sex stratified random sample of Palestinians and Israelis aged 25-74 years living in east and west Jerusalem was drawn from the Israel National Population Registry: 970 Palestinians and 712 Israelis participated. PA in a typical week was assessed by the Multi-Ethnic Study of Atherosclerosis (MESA) questionnaire. Energy expenditure (EE), calculated in metabolic equivalents (METs), was compared between groups for moderate to vigorous-intensity physical activity (MVPA), using the Wilcoxon rank-sum test, and for domain-specific prevalence rates of meeting public health guidelines and all-domain insufficient PA. Correlates of insufficient PA were assessed by multivariable logistic modeling. Results Palestinian men had the highest median of MVPA (4740 METs-min*wk-1) compared to Israeli men (2,205 METs-min*wk-1 p < 0.0001), or to Palestinian and Israeli women, who had similar medians (2776 METs-min*wk-1). Two thirds (65%) of the total MVPA reported by Palestinian women were derived from domestic chores compared to 36% in Israeli women and 25% among Palestinian and Israeli men. A high proportion (63%) of Palestinian men met the PA recommendations by occupation/domestic activity, compared to 39% of Palestinian women and 37% of the Israelis. No leisure time PA was reported by 42% and 39% of Palestinian and Israeli men (p = 0.337) and 53% and 28% of Palestinian and Israeli women (p < 0.0001). Palestinian women reported the lowest level of walking. Considering all domains, 26% of Palestinian women were classified as insufficiently active versus 13% of Palestinian men (p < 0.0001) who did not differ from the Israeli sample (14%). Middle-aged and elderly and less educated Palestinian women, and unemployed and pensioned Palestinian men were at particularly high risk of inactivity. Socio-economic indicators only partially explained the ethnic disparity. Conclusions Substantial proportions of Palestinian women, and subgroups of Palestinian men, are insufficiently active. Culturally appropriate intervention strategies are warranted, particularly for this vulnerable population.